Nutrient content of nyamplung seeds waste (Calophyllum inophyllum) after biofuel processing - Tri Mulya Hartati (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2012)
Like the rest of other agricultural wastes, waste from the process of making biofuels from nyamplung seeds (Calophyllum inophyllum Linn) also contain nutrients that can be utilized by both the soil and the plants and the soil as a source of plant nutrients. This study aimed to assess the nutrient content of the waste seed nyamplung after the process of Biofuel. This research was conducted in the Village District Ngade South Ternate Ternate, and the Laboratory of Soil Science Department of the Faculty of Agriculture UGM. This study used the descriptive method, which collect and analyze data and then interpret the results of laboratory analysis. Observed variables, including oil content and nutrient content of the waste, the content of total N, total P, total K, organic C, and KPK. The results showed that the biofuel seed crop nyamplung (Calopphyllum inophyllum Linn) have oil content of 46.57%, and biofuels from waste plant seeds contain nutrients: total N 1.43% (very high), 47.99% Organic C ( very high), total P 0.35% (very low), 1.30% total K (very low), C / N 33.78 (very high), and 17.93 KPK to 100 g-1 (medium).Key words: oil nyamplung, nutrient waste plant seeds nyamplung